2005
DOI: 10.1111/j.1365-2141.2005.05658.x
|View full text |Cite
|
Sign up to set email alerts
|

Genotype–phenotype correlation in MYH9‐related thrombocytopenia

Abstract: Summary Mutation of the non‐muscle myosin heavy chain type II‐A results in MYH9‐related hereditary macrothrombocytopenia (HMTC), including four autosomal dominant platelet disorders: May‐Hegglin anomaly (MHA), Sebastian (SBS), Fechtner (FS) and Epstein (EPS) syndrome. Denaturing high‐performance liquid chromatography (DHPLC) was optimised for rapid screening of the seven exons harbouring all but one of the previously reported mutations of MYH9. Individuals from 13 families with phenotypes suggestive of MYH9‐re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
74
0
3

Year Published

2006
2006
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(79 citation statements)
references
References 37 publications
2
74
0
3
Order By: Relevance
“…A mutation of MYH9 alone does not seem to cause associated Alport manifestations, and unknown genetic and/or epigenetic factors might influence the phenotypic consequences of MYH9 mutations. [7][8][9][10] Although the molecular mechanisms of hematologic abnormalities are under investigation, those of the kidney, cochlea, and lens are completely unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A mutation of MYH9 alone does not seem to cause associated Alport manifestations, and unknown genetic and/or epigenetic factors might influence the phenotypic consequences of MYH9 mutations. [7][8][9][10] Although the molecular mechanisms of hematologic abnormalities are under investigation, those of the kidney, cochlea, and lens are completely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…A mutation of MYH9 alone does not seem to cause associated Alport manifestations, and unknown genetic and/or epigenetic factors might influence the phenotypic consequences of MYH9 mutations. [7][8][9][10] Although the molecular mechanisms of hematologic abnormalities are under investigation, those of the kidney, cochlea, and lens are completely unknown.We previously showed that NMMHC-IIA polypeptide accumulates in neutrophil cytoplasm and forms inclusion bodies in patients with MYH9 disorders. The nature of the cytoplasmic accumulation can be classified according to the number, size, and shape of accumulated NMMHC-IIA granules, into types I, II, and III.…”
mentioning
confidence: 99%
“…18 The patients in this study demonstrated some or all of these symptoms (Table 1), in accordance with previous reports of variable effects of MYH9 mutations. [23][24][25] To determine the effect of these mutations on NK-cell cytotoxicity, eNK cells from these patients were prepared from peripheral blood and immediately evaluated for their ability to kill K562 erythroleukemia cells. Cytotoxicity of the NK-cell preparations was adjusted for purity of the patient and control NK-cell preparations, and the cytotoxic activity of each patient's NK cells was compared with the shipping control for the patient using lytic unit calculations to control for variability in shipping and assay conditions.…”
mentioning
confidence: 99%
“…Therefore, the name ''MYH9 disorder'' or ''MYH9-related disease'' has been proposed [15,[19][20][21]. To date, about 200 families with MYH9 disorders have been studied, in which 30 distinct mutations in the MYH9 gene have been identified [19][20][21][22]. The majority of patients are heterozygous for missense mutations and some patients are heterozygous for nonsense or frameshift mutation in the last exon.…”
Section: Related Disorders and Unsolved Issuesmentioning
confidence: 99%